STRUCTURAL BEHAVIOR OF STEEL-CONCRETE-STEEL SANDWICH STRUCTURE WITH NEW TYPE OF SHEAR CONNECTORS - Hayhder A. Abdul Razzaq (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ, 2019)
The aim of the current research is to investigate the structural behavior of steel-concrete-steel sandwich beams with a new suggested shear connectors. The shear connector was manufactured from deformed rebar in the form of stirrups. Four push out specimens were tested to obtain direct shear strength for the new type of shear connectors. Also four full size steel-concretesteel sandwich beams were tested under three points loading. All beams were simply supported. The experimental results showed three failure modes as follow: (1) flexural failure; (2) shearing of shear connectors; and (3) buckling in compression plate. The use of proposed shear connectors from deformed steel bars produces a good connection between steel plates and concrete core, where the load capacity of steel-concrete-steel beam with long leg stirrups (L. connector) is larger than other beams. The ultimate load of beam B1 (steel-concrete-steel sandwich beam with L. connector) is 0.125 greater than the ultimate load of beam B2 (steelconcrete-steel sandwich beam with J-hook connectors).